Peningkatan Physical health dalam Menunjang Performa Belajar - Nurkhoiroh, Nurkhoiroh; Hadjarati, Hartono; Haryanto, Arief Ibnu; Irawan, Safri; Haryani, Meri; Uno, Fadla; Puhi, Pasya Azahwa (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2025)
Permasalahan rendahnya konsentrasi belajar siswa kerap dikaitkan dengan kurangnya perhatian terhadap kesehatan fisik. Artikel ini membahas intervensi peningkatan physical health sebagai upaya menunjang performa belajar siswa di SMK Negeri 2 Gorontalo. Melalui metode Participatory Action Research (PAR), program pengabdian masyarakat dilaksanakan selama empat minggu dalam bentuk senam pagi yang menyenangkan dan rutin. Kegiatan ini melibatkan guru PJOK, 269 siswa, serta tim dosen dan mahasiswa, dengan frekuensi dua kali per minggu. Evaluasi dilakukan melalui angket konsentrasi belajar yang diisi saat pretest dan posttest. Hasil menunjukkan peningkatan skor rerata pada empat indikator utama: pemusatan perhatian (2,91 menjadi 3,52), sikap aktif (3,03 menjadi 3,46), minat belajar (3,03 menjadi 3,52), dan pemahaman materi (3,05 menjadi 3,49). Intervensi ini terbukti efektif dalam membentuk kebiasaan hidup sehat serta meningkatkan kesiapan mental dan kognitif siswa dalam proses pembelajaran. Artikel ini merekomendasikan integrasi aktivitas fisik ringan dalam rutinitas sekolah sebagai strategi peningkatan kualitas pendidikan menengah.Improving Physical health to Support Learning PerformanceAbstractLow student concentration is often linked to insufficient attention to physical health. This article discusses an intervention aimed at improving students' physical health to support learning performance at SMK Negeri 2 Gorontalo. Using the Participatory Action Research (PAR) method, a four-week community service program was conducted in the form of enjoyable and regular morning exercise sessions. The program involved Physical Education (PJOK) teachers, 269 students, and a team of lecturers and university students, with sessions held twice a week. Evaluation was carried out using a learning concentration questionnaire administered as pretest and posttest. The results showed improvements in four key indicators: attention focus (from 2.91 to 3.52), active behavior (from 3.03 to 3.46), learning interest (from 3.03 to 3.52), and material comprehension (from 3.05 to 3.49). This intervention proved effective in fostering healthy lifestyle habits while enhancing students' mental and cognitive readiness for learning. The article recommends integrating light physical activity into school routines as a strategy to improve the quality of secondary education.